Plasma levels of IL-6, IL-10, IL-18, TNFα under the conditions of tobacco intoxication and after treatment with aminophthalhydrazide - O. V. Alpidovskaya (Медицинская иммунология)
In response to damaging factors, a cascade of cytokines is released, triggering the processes of inflammation and fibrogenesis. The purpose of our study was to evaluate the levels of cytokines (IL-6, IL-10, IL-18, TNFα) in blood plasma under conditions of tobacco intoxication and with intramuscular administration of aminophthalhydrazide. The experiment was performed with 40 outbred white male rats. Intact group (n = 10) were in a priming chamber in absence of tobacco smoke. Experimental groups (1, 2, and 3) – n = 30, 10 animals in each group. The first and second groups of animals were exposed to tobacco smoke for one and two months. The third experimental group underwent intramuscular injections with sodium aminodihydrophthalazindione for 3, 7, 14 days. The content of IL-6, IL-10, IL-18, TNFα in blood plasma was determined by enzyme immunoassay technique. In 1st group, the TNFα level in blood plasma increased to 452.14±176.18 pg/mL (in intact animals, 15.23±3.13 pg/mL); in the 2nd group, this index decreased to 9.8; in group 3, these values showed a sharp increase (to 167.44±5.93 pg/mL). The level of IL-6 showed maximal values after 4 months of tobacco intoxication (group 3). The following IL-10 changes were observed: in the 1st group, its amounts increased by 1.2-fold; in the 2nd group a sharp decrease in the indindex was noted (13.7 times); in the 3rd group a decreased content of the cytokine was found (28.8 times) as compared with intact animals. After administration of aminodihydrophthalazinedione for 3 and 7 days, the content of TNFα showed sharp increas (14.8 times and 7.6 times, respectively); after 14 days of treatment, the level of TNFα decreased by 1.3 times compared to intact animals. We noted fluctuations in the levels of pro-inflammatory cytokines (IL-6 and IL-18). The level of IL- 10 in blood plasma had a statistically significant increase (5.3-fold at 3 days after drug administration); 8.2-fold 7 days after administration of the drug, and 23-fold after 14 days of treatment, as compared with the 3rd group. The plasma concentrations of TNFα, IL-6, IL-10, IL-18 showed sufficient changes under the conditions of tobacco intoxication. The immune response is characterized by increased levels of pro-inflammatory cytokines in blood plasma. Upon corrective therapy with sodium aminodihydrophthalazindione, an increase in the antiinflammatory IL-10 cytokine occurs, along with systemic decrease in the TNFα, IL-6, and IL-18 contents.